Tissue Expression Analysis, Cloning, and Characterization of the 5′-Regulatory Region of the Bovine LATS1 Gene - Wei, Dawei; Raza, Sayed Haidar Abbas; Wang, Xingping; Khan, Rajwali; Lei, Zhaoxiong; Zhang, Guijie; Zhang, Jiupan; Luoreng, Zhuoma; Ma, Yun; Alamoudi, Muna O.; Aloufi, Bandar Hamad; Alshammari, Ahmed Mohajja; et al. (Frontiers in Veterinary Science, 2022)
As a member of the large tumor suppressor (LATS) gene family, LATS1 plays an important role in regulating muscle growth and development. In this study, we determined the distinct exhibit patterns of tissue expression of bovine LATS1. Further, we determined the functional proximal minimal promoter of bovine LATS1 and identified the key transcription factors in the core promoter region to elucidate its molecular regulation mechanism. The results showed that bovine LATS1 was highly expressed in the longissimus thoracis and upregulation in infancy muscle. An electrophoretic mobility shift assay (EMSA) and chromatin immunoprecipitation (ChIP) assay in combination with site-directed mutation and small interfering RNA (siRNA) interference demonstrated that myogenic differentiation 1 (Myod1) and myocyte enhancer factor 2A (MEF2A) binding in the core promoter region (−298/−123 bp) play important roles in the transcriptional regulation of the bovine LATS1 promoter. Taken together, these interactions provide insight into the regulatory mechanisms of LATS1 transcription in mediating skeletal muscle growth in cattle.